Determinants of Access to Higher Education: Evidence from Jharkhand, India - Khalid Khan; Waseem Ahmad; Tabrez Alam (Statistika: Statistics and Economy Journal)
This paper examines the access to higher education across socio-religious groups in the state of Jharkhand in India. It also examines the factors affecting access to higher education and the role of students’ social background in explaining the inequality in participation in higher education. The analysis is based on cross tabulation, logistic regression and Fairlie decomposition method. The analysis shows that tribals, Muslims and Scheduled Castes are the worst performing groups in the state. The most prominent factor behind the vulnerable condition of tribals is their high concentration in rural areas as there is a remarkable gap in their performance between rural and urban areas. A large part of the gap between the privileged and the underprivileged groups could not be explained by endowment factors, namely, household size, education of the head of household and income background. The results suggest that incentives created due to family background leads to different outcomes among different socio-religious groups.